Relationship of age and scrotal circumference with the seminal characteristics of crossbred bulls - SUDHEER, S (The Indian Journal of Animal Sciences, 2014)
Ejaculates (562) were collected from 27 crossbred bulls aging 24 to 88 months to study the relationship of age and scrotal circumference on the seminal characteristics of bulls, Based on age and scrotal circumference, the bulls were divided into 3 groups respectively, There was a significant (P56m) compared to group 2 (44-56m) and group 1 (